Biological evaluation of molecules of the azaBINOL class as antiviral agents: Inhibition of HIV-1 RNase H activity by 7-isopropoxy-8-(naphth-1-yl)quinoline. Issue 16 (15th August 2019) - Overacker, Ross D.; Banerjee, Somdev; Neuhaus, George F.; Milicevic Sephton, Selena; Herrmann, Alexander; Strother, James A.; Brack-Werner, Ruth; Blakemore, Paul R.; Loesgen, Sandra
Graphical abstract: Highlights: A library of synthetic azaBINOLs was synthesized and screened for HIV-1 activity. AzaBINOLB#24 exhibited low-micromolar antiviral activity without cytotoxicity. AzaBINOLB#24 binds to HIV-1 reverse transcriptase and inhibits RNase H activity. NNRTI efavirenz andB#24 dosed together act additively. B#24 retains antiviral activity against a multi-drug resistant HIV-1 isolate. Abstract: Inspired by bioactive biaryl-containing natural products found in plants and the marine environment, a series of synthetic compounds belonging to the azaBINOL chiral ligand family was evaluated for antiviral activity against HIV-1. Testing of 39 unique azaBINOLs and two BINOLs in a single-round infectivity assay resulted in the identification of three promising antiviral compounds, including 7-isopropoxy-8-(naphth-1-yl)quinoline (azaBINOLB#24 ), which exhibited low-micromolar activity without associated cytotoxicity. The active compounds and several close structural analogues were further tested against three different HIV-1 envelope pseudotyped viruses as well as in a full-virus replication system (EASY-HIT). The in vitro studies indicated that azaBINOLB#24 acts on early stages of viral replication before viral assembly and budding. Next we exploredB#24 's activity against HIV-1 reverse transcriptase (RT) and individually tested for polymerase and RNase H activity. The azaBINOLB#24 inhibits RNase H activity and binds directly to the HIV-1 RT enzyme. Additionally, we observe additive inhibitory activity against pseudotyped viruses whenB#24 is dosed in competition with the clinically used non-nucleoside reverse transcriptase inhibitor (NNRTI) efavirenz. When tested against a multi-drug resistant HIV-1 isolate with drug resistance associated mutations in regions encoding for HIV-1 RT and protease, B#24 only exhibits a 5.1-fold net decrease in IC50 value, while efavirenz' activity decreases by 7.6-fold. These results indicate that azaBINOLB#24 is a potentially viable, novel lead for the development of new HIV-1 RNase H inhibitors. Furthermore, this study demonstrates that the survey of libraries of synthetic compounds, designed purely with the goal of facilitating chemical synthesis in mind, may yield unexpected and selective drug leads for the development of new antiviral agents.